Thrypticus atomus Frey 1915 ... - Grichanov, Igor Ya. (Zenodo, 2021)
Thrypticus atomus Frey, 1915 Material: 1♂, 25 km W Beryozovo, Vogulka, 63.9316 ° N, 64.5167 ° E, 19– 21.07.2018. Distribution: Type locality: Finland: Karislojo. Palaearctic: Austria, Belgium, Czech Republic, Finland, Hungary, Latvia, Netherlands, Sweden, Russia (Arkhangelsk, Krasnoyarsk, Leningrad, Pskov, Ryazan, Yakutia). New for Khantia-Mansia and West Siberia. ... : Published as part of Grichanov, Igor Ya., 2021, New records of Dolichopodidae (Diptera) from Khanty-Mansi Autonomous Region of Russia, pp. 4-11 in Amurian Zoological Journal XIII (1) on page 6, DOI: 10.33910/2686-9519-2021-13-1-4-11, http://zenodo.org/record/11088815 ...